The Development of SETS-Based E-Modules for Industrial Chemistry According to IMO Model Course 7.04 - Fajar Sari Kurniawan; Khoirotun Nafillah; Rahindra Bayu Kumara (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
The era of Industrial Revolution 4.0 encourages universities to utilize information technology. Learning industrial chemistry courses in maritime education is still conventional, with little time allocation. Apart from that, no digital-based learning resources comply with the IMO 7.04 standard. This research aims to develop a SETS (Science, Environment, Technology, and Society) based e-module Website for the Industrial Chemistry course according to IMO 7.04 standards, as well as analyze the feasibility of the product. This research method is R&D (Research & Development) using the ADDIE model but is limited to the development stage. Quantitative data is processed into interval data using a Likert scale. The research results show that the validation of material experts is 87.89% in the very valid category, and media experts are 91.67% in the very valid category. Limited trials on students showed a positive response 90.13% in the very good category. It is hoped that the development of this e-module can improve the quality of learning in maritime education.